Sliding wear behavior of Ni–Co–P multilayer coatings electrodeposited by pulse reverse method. (January 2020) - Karimzadeh, A.; Rouhaghdam, A. Sabour; Aliofkhazraei, M.; Miresmaeili, R.
Abstract: In this study, Ni–Co–P multilayer coatings were deposited using pulse reverse current. Alternative Co/P-rich and Co/P-poor layers were fabricated by alternation of cathodic duty cycle at 20 and 90% values. The layer thickness was altered within 3000–90 nm range. Coatings evaluation involved investigation of microstructure and chemical composition, microhardness, fracture toughness, and tribological measurements. The results showed that the thinning the layers enhanced the microhardness by up to 700 Hv and improved cracking resistance. Tribological study indicated that decreasing the layer thickness resulted in the friction coefficient lower than 0.4 and decreasing the mass loss and changing the wear mechanism from delamination to combined plastic deformation and abrasive wear. Higher loads led to oxidation and deformed layers on the wear track. Highlights: Multilayer coatings with different layer thickness deposited by pulse reverse method. Changing the duty cycle led to Co/P-rich and Co/P-poor alternative layers. Decreasing the layer thickness improved the hardness, wear and cracking resistance.